Structural Investigation of Betulinic Acid Plasma Metabolites by Tandem Mass Spectrometry - Roxana Ghiulai; Marius Mioc; Roxana Racoviceanu; Alexandra Prodea; Andreea Milan; Dorina Coricovac; Cristina Dehelean; Ștefana Avram; Alina D. Zamfir; Cristian V. A. Munteanu; Viviana Ivan; Codruța Şoica (Molecules, 2022)
Betulinic acid (BA) has been extensively studied in recent years mainly for its antiproliferative and antitumor effect in various types of cancers. Limited data are available regarding the pharmacokinetic profile of BA, particularly its metabolic transformation in vivo. In this study, we present the screening and structural investigations by ESI Orbitrap MS in the negative ion mode and CID MS/MS of phase I and phase II metabolites detected in mouse plasma after the intraperitoneal administration of a nanoemulsion containing BA in SKH 1 female mice. Obtained results indicate that the main phase I metabolic reactions that BA undergoes are monohydroxylation, dihydroxylation, oxidation and hydrogenation, while phase II reactions involved sulfation, glucuronidation and methylation. The fragmentation pathway for BA and its plasma metabolites were elucidated by sequencing of the precursor ions by CID MS MS experiments.